2017
DOI: 10.1007/978-3-319-67159-8_7
|View full text |Cite
|
Sign up to set email alerts
|

High-order Connectomic Manifold Learning for Autistic Brain State Identification

Abstract: Abstract. Previous studies have identified disordered functional (from fMRI) and structural (from diffusion MRI) brain connectivities in Autism Spectrum Disorder (ASD). However, 'shape connections' between brain regions were rarely investigated in ASD -e.g., how morphological attributes of a specific brain region (e.g., sulcal depth) change in relation to morphological attributes in other regions. In this paper, we use conventional T1-w MRI to define morphological connectivity networks, each quantifying shape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Hence, using a multi-order brain network representation (Zhao et al 2018; Lisowska and Rekik 2018a; Soussia and Rekik 2018) might enable a more comprehensive analysis of the neural basis of intelligence. Since the brain connectome can be derived from several MR imaging modalities (e.g., diffusion tensor imaging, T1-weighted, fMRI), one can integrate other network types such as structural connectomes (Cammoun et al 2012) and morphological brain networks (Soussia and Rekik 2017;Lisowska et al 2017;Mahjoub et al 2018;Zhou et al 2018) in a unified framework to examine brain-intelligence in a more holistic manner. Comparatively, we used whole-brain connectivity measures for the identification of ROIs in relation to IQ scores for both cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, using a multi-order brain network representation (Zhao et al 2018; Lisowska and Rekik 2018a; Soussia and Rekik 2018) might enable a more comprehensive analysis of the neural basis of intelligence. Since the brain connectome can be derived from several MR imaging modalities (e.g., diffusion tensor imaging, T1-weighted, fMRI), one can integrate other network types such as structural connectomes (Cammoun et al 2012) and morphological brain networks (Soussia and Rekik 2017;Lisowska et al 2017;Mahjoub et al 2018;Zhou et al 2018) in a unified framework to examine brain-intelligence in a more holistic manner. Comparatively, we used whole-brain connectivity measures for the identification of ROIs in relation to IQ scores for both cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Representing a shape as a multi-directional varifold has several appealing properties. First, it captures complex shape patterns through exploring its local neighborhood in comparison to conventional cortical measures (e.g., cortical thickness) used in [4, 5]. Second, it allows to perform shape matching without the need to establish point-to-point correspondence between two shapes.…”
Section: Estimation Of Shape and Growth Brain Network Atlasesmentioning
confidence: 99%
“…However, while providing tools for quantifying connections between different neuroanatomical structures, conventional connectomics tools are not particularly designed to investigate the morphology (or shape) of the brain and its dynamic changes with time (e.g., cortical growth and cortical atrophy). Specifically, ‘shape-to-shape’ connections, where we measure the morphological similarity between the brain structure shape and another brain structure shape, are rarely explored in the neuroscience state-of-the-art –with the exception of recent works introducing cortical morphological networks for brain disorder diagnosis [4, 5]. Previous works showed that brain morphology can be affected by different psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…However, existing works mainly used functional networks (derived from rsfMRI) and structural networks (derived from dMRI). These exclude the recent landmark works [4][5][6], which devised morphological brain networks (MBN) for mapping morphological 'connections' in the cortex. Basically, an MBN is generated by measuring the difference in morphology between two cortical regions based on a specific cortical attribute (e.g., sulcal depth).…”
Section: Introductionmentioning
confidence: 99%